Pengelolaan Manajemen Mutu Sumber Daya Manusia Dalam Pendidikan Islam Di SMP IT Qurrata A’yun Batusangkar - Dini Febriyenti; Saputra, Roni; Zulmuqim, Zulmuqim (LP2M Universitas Islam Ahmad Dahlan, 2023)
This article discusses the management of HR quality management at SMPIT Qurrata A'yun Batusangkar. Because researchers use descriptive methods, this research is included in the qualitative research category. Data was collected through official and personal documentation, interviews and observations. The research results show that human resource planning at SMP IT Qurrata A'yun Batusangkar in Human Resource Quality Management consists of evaluating needs, setting human resource goals and policies, designing and implementing plans, and supervision. The process of supervising human resources at SMP IT Qurrata A'yun Batusangkar in Human Resource Quality Management includes class visits and supervision of learning tools. Implementation of human resources also includes recruitment, selection, placement of teaching staff and educational staff, training and development, and performance assessment